Elastosis in Actinic Cheilitis. Literature Review - Boza Oreamuno DDS, MSc, Yadira V.; Rojas DDS, PhD, Isolde G. (Odovtos - International Journal of Dental Sciences, 2018)
The extracellular matrix (ECM) plays an important role in the regulation of biological events, such as cell migration, proliferation and differentiation. Chronic exposure to ultraviolet (UV) light causes elastosis (to varying degrees), which corresponds to a basophilic degeneration of the ECM. Actinic cheilitis (AC) is a potentially malignant lip lesion induced by regular and prolonged exposure to UV light, which mainly affects the vermilion. AC lesions have a complex stroma characterized by the presence of elastosis, chronic inflammatory infiltrate of different intensity and the appearance of telangiectatic blood vessels. Within this inflammatory infiltrate a significant increase of mast cells (MCs) has been described, located especially around areas of elastosis and at the subepithelial zone. It has been proposed that actinic elastosis is produced both, by degenerative processes and by abnormal synthesis of elastic fibers by photodamaged fibroblasts, which is accompanied by morphological changes in collagen. Although the fibroblast would play a major role in actinic elastosis formation, several studies suggest that other cell types such as MCs also contribute significantly to actinic ECM damage. The purpose of this review is to discuss the characteristics of elastosis in AC.